Pollination efficiency of the stingless bee Melipona subnitida on greenhouse sweet pepper - Cruz, Darci de Oliveira; Freitas, Breno Magalhães; da Silva, Luis Antônio; da Silva, Eva Mônica Sarmento; Bomfim, Isac Gabriel Abrahão (Pesquisa Agropecuaria Brasileira, 2005)
The present study was carried out in Northeastern Region of Brazil, in order to investigate the use of stingless bee Melipona subnitida Ducke in the pollination of greenhouse sweet pepper (Capsicum annuum L.). Treatments of hand cross-pollination, hand self-pollination, pollination by bees and restricted pollination were performed. Results showed that despite sweet pepper flowers are considered autogamous, this crop benefits from pollination by M. subnitida, producing fruits significantly heavier and wider, containing a greater number of seeds and of better quality (lower percentage of malformed fruits) than self-pollinated sweet pepper. Thus, M. subnitida can be considered an efficient pollinator of greenhouse sweet pepper.